Análise geoambiental da sub-bacia do Rio Pomonga em Sergipe - Souza, Acacia Maria Barros (2015)
The technological advances made by man, especially in the course of the twentieth century, materialized by the increase in population growth, industrial expansion, among other conditions, caused an overload to the natural environment. This intense development has provoked considerable social and environmental changes in spacewhere they are represented by a worrisome unbalance of ecosystems. From this perspective, the present study aims to analyze the environmental and socioeconomic aspects of thesub watershed of the river Pomonga to support the ordering and management of the territory. For the fulfillment of this and other specific objectives were used different methodological procedures, standing out among thembibliographic and cartographic documents survey, drawing up ofthematics letters.The geosystem is constituted in the methodological basis of this study because prioritize the integration between the various landscape elements present in the sub watershed system, and the relationship with society. The results of these studies show that the systemic approach applied in the sub watershedin question, possibilited an understanding on how his environmental organization,economic and spatial.Initially, it was noted in the landscape the fragility of municipal administrations in establishing criterion for the use and occupation of space, mainly to sense a balance between environmental conservation and economic development.So, in general it was found that although the incidence of economic activities subject to pollutants on the banks of river Pomonga, such as shrimp farming, water still remains with acceptable levels of quality.